From national to local: A geodemographic segmentation model for market targeting in Vietnam's major cities - Nguyen Ngoc Son; Chau Bao Anh; Thu Hang Le; Vu Anh Duc (Sustainable Futures)
Spatial analysis, particularly through geodemographic segmentation, has emerged as a critical determinant for enterprise strategic decision-making in market entry, exploitation, and expansion. This study contributes to the under-explored field of geodemographic segmentation in Vietnam by developing a robust model. By employing a combination of Principal Component Analysis (PCA) and K-means clustering, the research examined a comprehensive set of demographic variables (population, housing, marital status, educational attainment) across 11,165 administrative units. This analysis resulted in the segmentation of these units into 15 distinct clusters based on their characteristics. Subsequently, the model was further refined by focusing on major cities like Hanoi, Da Nang, and Ho Chi Minh City, integrating both geographic and demographic variables for a market segmentation analysis. Owing to its focus on practical application, this study is anticipated to be a pioneering effort in the Vietnamese context, paving the way for the exploration of geodemographic segmentation models across diverse industries such as banking, retail, food, and hospitality.